2012
DOI: 10.1001/archfacial.2012.147
|View full text |Cite
|
Sign up to set email alerts
|

Versatile Applications of the Polydioxanone Plate in Rhinoplasty and Septal Surgery

Abstract: The polydioxanone plate is a safe and reliable absorbable implant that has many different applications in rhinoplasty and septal surgery. It not only acts as a scaffold but also stimulates and guides cartilage regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
48
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 13 publications
0
48
0
Order By: Relevance
“…The increasing use of PDO nano-fibers for cosmetic and other purposes [4][5][6][7][8][9][10] makes it imperative to understand its effect on the immune system. Our data suggests that PDO has no adverse effect on the functions of PMNs, monocytes and NK cells in humans ( Figure 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increasing use of PDO nano-fibers for cosmetic and other purposes [4][5][6][7][8][9][10] makes it imperative to understand its effect on the immune system. Our data suggests that PDO has no adverse effect on the functions of PMNs, monocytes and NK cells in humans ( Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…The non-toxic and biodegradable nature of PDO has led to the use of PDO nano-fiber scaffolds for antimicrobial drug delivery system for regenerative endodontics [7]. PDO plates and scaffolds are also being used for cosmetic procedures such as rhinoplasty and septal surgery where they guide cartilage regeneration [8].…”
Section: Introductionmentioning
confidence: 99%
“…The absence of further retraction underscores the excellent structural support obtained by the PDS. For many years, this versatile material has shown its worth as a substitute for cartilage or bone grafting during orbital floor reconstruction and rhinoplasty/septoplasty procedures [14,15,19], primarily due to its histoconductive properties [11,20], which stimulate bone or cartilage regeneration. Animal studies have demonstrated that thin PDS plates are reabsorbed within 25 weeks [11], which give enough healing time at the dome junction while the PDS plate acts as a template for new cartilage formation, preventing undesirable secondary deviations.…”
Section: Discussionmentioning
confidence: 99%
“…Its use for scaffolding purposes obviates the need for other graft techniques or additional cartilage donor site surgery. There are compelling data regarding the safety and efficacy of this versatile material [12], including during rhinoplasty with and without septoplasty [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…6 Polydioxanone plates are made of a colorless crystalline resorbable biopolymer that is fully degraded by hydrolysis and metabolized by the body. 6 The material typically works to scaffold a graft in place while healing occurs, but has also been identified to stimulate cartilage growth. 7 Polydioxanone plates are available in multiple thicknesses, including 0.15-mm perforated, 0.25-mm unperforated, and 0.55-mm unperforated.…”
mentioning
confidence: 99%